Frequency of Thyroid Cancer at King Fahad Hospital, Madinah (Medical Forum Monthly, 2024)
Objective: To assess the frequency of common thyroid cancer at king Fahad Hospital, Madinah. Study Design: Retrospective study.Place and Duration of Study: This study was carried out on all the patients treated for Cancer of Thyroid Gland, at King Fahad Hospital (KFH)-Madinah between Jan 2009 to February 2012.Patients and Methods: Ninety-one patients diagnosed with Cancer of Thyroid of various Age, Sex & Races were registered with King Fahad Hospital Madinah.Results: 75% patients were Saudi nationals, 10 % patients were from other Arab countries and the remaining 15 % were non-Arabs. There were 72% females and 28% Males . The Ages ranged from 14 years to 94 years. 34% of these patients were less then 30 years of Age at the time of the diagnosis. Over 90 % of the cases presented with Swelling Anterior Neck while in other 10% of the cases Dysphagia or Dyspnoea with Rt. or Lt. supraclavicular masss/swelling was the major complaint. 71% patients under went various surgical procedures for the Neck swelling. The Total Thyroidectomy was done in 48% patients . The Histology revealed 52 % of pure Papillary Carcinoma and 23 % were of Follicular origin. Majority of the diagnosed patients of Ca. Thyroid were referred to King Faisal Specialist Hospital Riyadh for Radioactive Iodine Ablation Therapy. The follow-up was poor as patients were from highly mobile population and belonged to Nine different countries.Conclusion: The study reveals that the presentation of Ca. Thyroid in our series is essentially similar to what has been reported from other parts of the world.